Health sciences faculty perception and practices on OA scholarly communication - Lwoga, Edda Tandi (My University, 2013)
This study sought to investigate the faculty’s awareness, attitudes and use of open scholarly communication in Tanzanian health sciences universities. Based on a questionnaire survey, 415 faculty members were selected through a stratified random sampling from a population of 679 in all eight health sciences universities in Tanzania. The response rate was 71.1%. The study found a high level of engagement with scholarly publishing, where senior members were more likely to participate in scholarly communication as journal authors, referee and editors. The majority of respondents were aware about open access (OA) issues; however, a small proportion of faculty’s research materials was made available in OA. Senior faculty with more proficient technical skills are more likely to use OA than junior faculty. Major barriers to OA usage were related to ICT infrastructure, awareness, skills, journal author pay model, and copyright and plagiarism concerns. This study recommends the following: universities to improve information and communication technology infrastructure, and develop institutional repositories and policies, and librarians to create awareness about OA, conduct information literacy programmes, and provide information services on copyright management issues and other related OA aspects. This is first comprehensive and detailed study focusing on the health sciences faculty use behaviour of OA initiatives in Tanzania, and reveals findings that are useful for planning and implementing OA initiatives in other institutions with similar conditions.
Keywords: OA; scholarly communication; health sciences; faculty; Tanzania; HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::African and comparative archaelogy